Hemodynamic changes during conventional and daylight photodynamic therapy of actinic keratoses – a randomized controlled trial. (3rd October 2022) - Hartmann, J.; Keller, A.; Enk, A.; Gholam, P.
Abstract: Background: Photodynamic therapy (PDT) is an effective treatment for actinic keratosis (AK). However, pain and hypertension are important side effects of conventional PDT (c-PDT). Several studies have demonstrated that daylight PDT (dl-PDT) is less painful while being as effective as c-PDT. Objective: To observe the effect of c-PDT and dl-PDT on different hemodynamic parameters (systolic blood pressure and diastolic blood pressure, pulse rate, and peripheral oxygen saturation). Methods: Fifty patients with AK on the head were enrolled into this prospective, randomized, controlled study and treated with c-PDT or dl-PDT in a 1:1 ratio. Hemodynamic parameters were measured at four different time points during treatment. Pain was quantified using a visual analog scale. AK was counted before treatment and after one month. Results: C-PDT is associated with significantly more pain, a significant increase in blood pressure and a higher rate of patients with grade 3 hypertension. Whereas dl-PDT is almost painless and does not lead to any changes in hemodynamic parameters. For both treatments, a similar lesion response rate was found after one month. Conclusions: dl-PDT has a better tolerability while being as effective as c-PDT and therefore may be the more favorable treatment option in certain patient groups.